Peer effects and textbooks in primary education: Evidence from francophone sub-Saharan Africa - Markus Frölich; Katharina Michaelowa (Hamburg Institute of International Economics (HWWA), 2004)
As opposed to many other school inputs, textbooks have frequently been demonstrated to significantly foster student achievement. Using the rich data set provided by the 'Program on the Analysis of Education Systems' (PASEC) for five francophone, sub-Saharan African countries, this paper goes beyond the estimation of direct effects of textbooks on students' learning and focuses on peer effects resulting from textbooks owned by students' classmates. Applying and extending nonparametric estimation methods from the treatment evaluation literature we separate the direct effect of textbooks from their peer effect. The latter clearly dominates but depends upon the initial level of textbook availability.
Keywords: O15; C21; C14; 330; primary education; student achievement; evaluation; nonparametric estimation; Allgemeinbildende Schule; Lehrmaterial; Unterricht; Schwarzafrika; Peer effect